2019
DOI: 10.1371/journal.pone.0224377
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive contrast enhanced ultrasound molecular imaging of inflammation in autoimmune myocarditis for prediction of left ventricular fibrosis and remodeling

Abstract: BackgroundMyocarditis can lead to myocyte loss and myocardial fibrosis resulting in dilated cardiomyopathy (DCMP). Currently employed methods for assessing the risk for development of DCMP are inaccurate or rely on invasive myocardial biopsies. We hypothesized that molecular imaging of tissue inflammation with contrast enhanced ultrasound during peak inflammation in myocarditis could predict development of fibrosis and impaired left ventricular function.Methods and resultsExperimental autoimmune myocarditis (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…For binary mixtures, the components were generally dissolved and premixed in organic solvent first, then dried to form a lipid film, and dispersed in aqueous medium before microbubbles were produced ,, (i.e., indirect method). For ternary mixtures, the components were generally dispersed directly in aqueous medium before microbubble production , (i.e., direct method). Based on the effect of cooling rate on microstructures in large microbubbles (>10 μm) after microbubble production, we hypothesize that the method of handling the lipids prior to microbubble production may also influence the ligand distribution and/or lipid phase in the coating of microbubbles.…”
Section: Introductionmentioning
confidence: 99%
“…For binary mixtures, the components were generally dissolved and premixed in organic solvent first, then dried to form a lipid film, and dispersed in aqueous medium before microbubbles were produced ,, (i.e., indirect method). For ternary mixtures, the components were generally dispersed directly in aqueous medium before microbubble production , (i.e., direct method). Based on the effect of cooling rate on microstructures in large microbubbles (>10 μm) after microbubble production, we hypothesize that the method of handling the lipids prior to microbubble production may also influence the ligand distribution and/or lipid phase in the coating of microbubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial fibrosis is a typical characteristic observed during the transition of myocarditis to DCM ( 43 ). A previous study reported the contribution of Smad-dependent signaling pathways to TGF-β-induced cardiac fibrosis ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental autoimmune myocarditis (EAM) animal models largely mimic pathological cardiac damage caused by acute-onset myocarditis in humans. [32][33][34] Therefore, EAM mice on day 21 of immunization were selected for subsequent studies. Therefore, multimodal imaging (US/CMR/PA imaging) is highly desirable (Fig.…”
Section: Introductionmentioning
confidence: 99%